Spatial distribution of physical attributes of an Ultisol under papaya crop - Lima, Juliao Soares de Souza; Sturião, Walas Permanhane; Gontijo, Ivoney; Silva, Samuel Assis (Comunicata Scientiae, 2018)
The successful development of the root system of plants depends on the favorable conditions of soil physical attributes. The objective of this work was to study the spatial variability of physical attributes in an Ultisol cultivated with papaya. The soil was prepared mechanically plowing, harrowing, sulcal and subsoiler. In the center of the crop field was built a sampling grid with points spaced 5.7 m, totalizando129 georeferenced points. The soil samples at two depths (0 - 0.20 m, 0.20 - 0.40 m) were collected for four months after transplantation, to determine the total porosity (TP), soil moisture (Um), soil bulk density (BD) and soil penetration resistance in the planting row (PRPR) and in the traffic machines rows (PRRow). The soil penetration resistance in the planting row and in the traffic machines row was determined. The BD1 and BD2 showed the lowest CV values, and the data were fitted to the exponential and spherical models, respectively, with spatial dependence ranges of 20 and 28 m. At the layer of 0-0.20 m depth, the attributes showed the same spatial distribution pattern. At the layer of 0-0.20 m depth, the soil penetration resistance showed 7.5 times greater in the traffic machines region (rw spacing) than the value found in the planting row.